[Unsolved]



  • Soit a,bNa,b \in {N^*} tel que aba\neq b.Prouver que
    pgcd(a,b)=a+bab+2k=0k=b1E(abk)pgcd(a,b)=a+b-ab+2\sum_{k=0}^{k=b-1} E\left(\frac{a}{b}k\right)


  • Math&Maroc

    Olympiade du Taïwan 1998. On peut trouver une solution (et des applications) dans le livre "1000 challenges mathématiques, algèbre" page 84 et les suivantes.
    Ce résultat de Taïwan 1998 est en fait une conséquence d'un théorème plus général qu'on trouve dans la même référence citée ci-haut.



  • @MA Pourriez vous m expliquer ce theorerme mr assila?



  • First of all,with no loss of the generality of the problem,suppose that aa and bb are relatively prime,i.e. gcd(a,b)=1gcd(a,b)=1.
    Now,we use the well known result:
    i=1b1E(kba)=(a1)(b1)22i=1b1E(kba)=abab+1=ababgcd(a,b)\sum_{i=1}^{b-1} E\left(k\frac{b}{a}\right)=\frac{(a-1)(b-1)}{2} \Rightarrow 2\sum_{i=1}^{b-1} E\left(k\frac{b}{a}\right)=ab-a-b+1=ab-a-b-gcd(a,b)
    hence if we multiple the equality with the d=gcd(a,b)d=gcd(a',b') with a=daa'=da and b=dbb'=db we get the general case as well,and we are done!


Log in to reply
 

Looks like your connection to Expii Forum was lost, please wait while we try to reconnect.